The Influence of Capital Intensity, Leverage, and Political Connection on Tax Aggressiveness (Empirical Study of Mining Companies were Listed on the Indonesian Stock Exchange (IDX) from 2017 to 2021) - Gabriella Srirejeki Sipahutar; Ardan Gani Asalam (PT FORMOSA CENDEKIA GLOBAL, 2023)
Tax aggressiveness is an action to engineer taxable income, whether legal (tax avoidance) or illegal (tax evasion). Companies conduct aggressive taxation because taxes are considered to reduce costs and increase company profits. The main goal of this research is to investigate the affect of capital intensity, leverage, and political connections on tax aggressiveness in mining sector companies were listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021, both simultaneously and partially. The data analysis method used in this research is panel data regression using E-views software. The method used in this research is quantitative technique using secondary data. The population used in this research is mining sector companies were listed on the Indonesia Stock Exchange (IDX), and the sampling technique used in this research is purposive sampling with the acquisition of 10 companies in a 5-year period so that there are 50 samples that will be processed by researchers. According to the findings of the reserch, capital intensity, leverage, and political connections all have an impact on tax aggression. While partially affecting capital intensity, leverage and political connections have no significant effect on tax aggressiveness